English and international students in China today: A sociolinguistic study of English-medium degree programs at a major Chinese university. Issue 1 (10th December 2015) - Botha, Werner
Abstract : China has since 2000 started marketing itself as a hub for international education, and there has been a push by the government to attract a large number of foreign students to the country's universities. Sharma (2011) reported that there were around 260, 000 foreign students studying in China's universities, and that the aim of the Ministry of Education was to attract around 500, 000 foreign students by 2020. However, as China is a so-called 'emerging destination' for foreign students, perhaps not surprisingly, the vast majority - around two-thirds - of its foreign student population is currently from the Asia region (Study in China, 2012). Although the largest number of foreign students in China study Chinese language programs, an increasing number are attracted by such programs as engineering and medicine. These courses are also being promoted as English-medium programs, with whole degree programs offered from undergraduate to postgraduate levels in English. Little research has been carried out on how these programs are being conducted, the reception of these programs by foreign students in China, and the impact this is having on China's universities. The attraction of international students to China's higher education institutions would no doubt alter the dynamics of language use on these university campuses. This article reports on the reception and use of English by foreign university students in one such international degree program: international undergraduate students studying for a degree in Bachelor of Medicine and Bachelor of Surgery (MBBS) in the School of Medicine of one of China's leading universities. This case study provides an example of how English-medium instruction programs are currently being used to attract foreign students to China's universities, partly in order for these universities to promote themselves as 'international' institutions (see also Botha, 2014; and Bolton and Botha, 2015).